Analysis of the Influence of Service Quality, Price Perception, Location, Facilities, and Promotion on Consumer Interest in Choosing a Fitness Center - Eko Prasojo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aimed to determine and analyze the influence of Quality of Service, perception of price, location, Facilities, and Promotion partially and simultaneously on consumer buying interest. The population used is a permanent member of Life Gym Fitness Yogyakarta. The population in this study in which the total number of permanent members of the Life Fitness Gym Yogyakarta numbered 525 members. The sample in this study is consumers who simply doing fitness in Life Gym Fitness Yogyakarta, totaling 84 permanent members of the Life Fitness Gym Yogyakarta. The technique used is purposive sampling; the sampling criteria were decent, eligible members of Life Gym Fitness Yogyakarta who have coached in the body fitness Life Fitness Gym Yogyakarta at least 2 times within 1 month before the study. The analysis tool used is Multiple Regression Analysis. Based on the test results F, variable quality of service, perception of price, location, facilities, and promotion simultaneously influence Consumer Interests in the Electoral Buy at Life Fitness Center Gym Yogyakarta. Based on the t-test results, the variables quality of service, location, and Promotion partially influence consumer purchase interest. While the perception of price variables and partial facilitiesdo not influence consumer purchase interest and the magnitude of the coefficient of multiple determination (Adjusted R ²) of 0.302, it means that 30.2% of the Interests Buy Consumers in the selection of Life Fitness Center Gym in Yogyakarta influenced by five variables free which consists of Quality of Service, perception of price, location, facilitiesand Promotions.